Thromboelastography maximum amplitude as an early predictor of disseminated intravascular coagulation in patients with heatstroke. (31st December 2022) - He, Longping; Lin, Qingwei; Zhong, Lincui; Zeng, Qingbo; Song, Jingchun
Abstract: Objectives: The aim of this study was to investigate the ability of TEG to predict DIC associated with heatstroke. Methods: We carried out a retrospective, single-center study of 67 patients with heatstroke admitted to an intensive care unit (ICU) at a comprehensive hospital between July 2016 and August 2021. Conventional coagulation tests (CCTs) and TEG were performed within 2 h of admission in ICU. Patients were diagnosed with DIC based on International Society of Thrombosis and Hemostasis criteria, and those with or without DIC were compared in terms of CCTs and TEG findings. The ability of individual parameters to predict DIC was assessed based on logistic regression and the area under receiver operating characteristic curves (AUC). Results: Of the 67 patients, 19 (28.4%) were diagnosed with DIC. Compared to patients without DIC, those with DIC had significantly longer reaction time [14.5(10.6–26.0) vs. 6.2(5.1–10.1)min]( p  < 0.001) and kinetic time [10.9(5.9–25.0) vs. 2.7(2.2–4.7) min]( p  < 0.001). Conversely, those with DIC had significantly lower alpha angle [22(9.1–43.3) vs. 55.0(44.8–61.7)°]( p  < 0.001), maximum amplitude (MA) [(26.9(17.7–41.4) vs. 52.2(45.8–58.1) mm)] ( p  < 0.001) and coagulation index [-17.3(-39 to −7.9）vs. −2.4(-6.2to-0.6)]( p  < 0.001). MA at a cutoff value of 45.4 mm gave an AUC of 0.9 for predicting DIC, with sensitivity of 77.1%, specificity of 89.5%, positive predictive value of 10.5% and negative predictive value of 22.9%. Multifactorial logistic regression identified MA < 45.4 mm as an independent predictor of DIC (odds ratio 9, 95% confidence interval 1.2-69.2, p  = 0.035). MA decreased significantly as DIC score increased and was significantly lower in the non-survivors on admission. Conclusions: MA < 45.4 mm in patients with heatstroke may predict elevated risk of DIC. Highlights: Patients with heatstroke-induced disseminated intravascular coagulation (DIC) has high mortality. A retrospective, single-center study was performed to investigate the ability of thromboelastography (TEG) to predict DIC associated with heatstroke. The maximum amplitude (MA) value of TEG decreased significantly with the increase of DIC score. MA < 45.4 mm was firstly demonstrated to an independent predictor of heatstroke-induced DIC.